Headache in the elderly: a clinical study - Lisotto, C. (Springer-Verlag, 2004)
Although the prevalence of headache in the elderly is relevant, until now few studies have been conducted in patients over the age of 65 years. We analyzed the clinical charts of 4,417 consecutive patients referred to our Headache Centre from 1995 to 2002. There were 282 patients over 65 years of age at the first visit, corresponding to 6.4% of the study population. Primary headaches were diagnosed in 81.6% of the cases, while secondary headaches and non-classifiable headaches represented, respectively, 14.9% and 3.5% of the cases. Among primary headaches, the prevalence was almost the same for migraine without aura (27.8%), transformed migraine (26.1%) and chronic tension- type headache (25.7%). The most frequent secondary headaches were trigeminal neuralgia and headache associated with cervical spine disorder.